Understanding the experience and multidimensional needs of Ugandan patients with advanced heart failure - Namukwaya, Elizabeth Kiwuuwa (The University of Edinburgh, 2016)
Background: The burden of non-communicable diseases including cardiovascular diseases such as heart failure in Africa is rising rapidly, and they are now recognised as a significant cause of morbidity and mortality in the continent. Heart failure causes significant multidimensional impact (physical, social, psychological and spiritual), even with the advent of medicines that offer mortality benefit. Comprehensive care for heart failure must include palliative care that addresses multidimensional needs in line with patient-centered care. However, most research on heart failure in Africa has not explored these multidimensional needs from the patients’ perspective, and palliative care is still seen as being for those with cancer and HIV/AIDS. Aims: To understand the multidimensional experiences, needs, and use of services by patients with heart failure during their disease trajectory. To understand health care professionals’ perceptions of patients’ needs, the care required and the availability of services for patients with advanced heart failure in Uganda. Methods: A total of 48 face to face qualitative longitudinal interviews (36-patient alone, 4 paired-patient and family carer, 8 with bereaved carers), were conducted with 21 patients with stage 3 or 4 heart failure being treated in Mulago Hospital and some of their family carers. Patient interviews were followed by the administration of the African Palliative Care Association African Palliative Outcome Scale supplemented with the broader symptom assessment tool the POS-S. Patients were interviewed during the time of hospitalisation when the researcher first made contact with them, and were followed up monthly by phone. Longitudinal interviews were conducted at 3 and 6 months after the first interview if their clinical condition remained stable, and earlier if there were major concerns or changes in their multidimensional experiences. Eight single interviews were conducted with health professionals (5 doctors, 2 nurses and 1 social worker) involved in the care of the patients. All interviews were audio recorded, and those of the health professionals transcribed verbatim, those of the patients were first translated to English and transcribed and all were exported into QSR Nvivo software version 10 for analysis. Principles from Charmaz’s grounded theory (line by line coding, focused coding, constant comparison and theoretical coding) were employed for analysis. Findings: The patients’ experience was that of learning to live with the unknown in a life dominated by symptoms despite, and because of, treatments. The impact of the various symptoms limited physical performance leading to multiple losses. Presence of a high level of health illiteracy, lack of information on their illness coupled with a high reliance on local cultural beliefs to make health decisions, led to the following: delayed recognition of illness and seeking of care; inappropriate self- care and poor adherence to medications; poor understanding of illness and its prognosis; unrealistic expectations of treatment; and inappropriate choices of where to seek care. Patients were often faced with health system challenges that contributed to late diagnosis and exacerbated the problem of poor adherence to treatment because of lack of medicines and lack of information. The illness impact was also observed in the social, psychological and spiritual domains of patients’ lives causing anxiety and worry, isolation, rejection and stigma, spiritual pain and spiritual growth. Patients expressed the need for normal functioning, information, to be in control and to be facilitated to cope and adapt to the unknown. Patients employed different mechanisms of coping and adaptation, with hope being central in coping as they tried to live with the unknown. Patients suggested changes to the health system and in the conduct of health professionals to improve future care. Health professionals were able to recognise the multidimensional impact of the illness on the patients, but the details of the concerns tended to differ for the patients and health professionals. Health professionals’ proposals on improving care tended to emphasise interventions that would improve physical care as opposed to the other dimensions. Conclusion: This is the first qualitative longitudinal research in Uganda that has explored the experiences of patients with advanced heart failure to gain an understanding of their needs and concerns from their perspective over the course of their illness. Many concerns such as a lack of information, challenges with coping, the symptom experience and its impact on function and the psychological, social and spiritual aspects of their lives are enduring in literature. However, this study also identified other concerns less common in the literature that could have led to a unique illness experience. These included: health system challenges; the impact of culture; beliefs and poverty; and a high level of health illiteracy.
Keywords: experiences; needs; heart failure; longitudinal study; Uganda